Management of a university ambulatory service: nursing in the coping of the pandemic of COVID-19 - Raíla de Souza Santos; Carla Tatiana Garcia Barreto; Patrícia Ferraccioli Siqueira Lemos; Cíntia Araujo Duarte; Diego da Silva Moreira; Adriana Teixeira Reis; Fernanda Henriques da Silva; Alessandra Sant'Anna Nunes
ABSTRACT Objective: to describe the implementation and management of a restructured nursing service to cope with the COVID-19 pandemic. Methods: a descriptive study, carried out at Piquet Carneiro Polyclinic, a university ambulatory unit, which became a reference for testing the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the city of Rio de Janeiro. Results: dimensioning of human resources for nursing was carried out; flows for serving users of the unit and for testing SARS-CoV-2; professional training on prevention practices. From March 18 to July 3, a total of 31214 services were made by the nursing team, 25424 for testing and 453 health professionals received professional training. Final considerations: nursing represents an important workforce, planning and management for restructuring health services in an emergency, due to its broad managerial, educative and direct care to the population.